Marked aggravation of pyrethroid resistance in major malaria vectors in Malawi between 2014 and 2021 is partly linked with increased expression of P450 alleles - Benjamin D. Menze; Magellan Tchouakui; Leon M. J. Mugenzi; Williams Tchapga; Micareme Tchoupo; Murielle J. Wondji; Martin Chiumia; Themba Mzilahowa; Charles S. Wondji (BMC Infectious Diseases, 2022)
Abstract Background Increased intensity of pyrethroid resistance is threatening the effectiveness of insecticide-based interventions to control malaria in Africa. Assessing the extent of this aggravation and its impact on the efficacy of these tools is vital to ensure the continued control of major vectors. Here we took advantage of 2009 and 2014 data from Malawi to establish the extent of the resistance escalation in 2021 and assessed its impact on various bed nets performance. Methods Indoor blood-fed and wild female Anopheles (An) mosquitoes were collected with an electric aspirator in Chikwawa. Cocktail and SINE PCR were used to identify sibling species belonging to An. funestus group and An. gambiae complex. The susceptibility profile to the four classes of insecticides was assessed using the WHO tubes bioassays. Data were saved in an Excel file. Analysis was done using Vassarstats and figures by Graph Pad. Results In this study, a high level of resistance was observed with pyrethroids (permethrin, deltamethrin and alpha-cypermethrin with mortality rate at 5x discriminating concentration (DC) < 50% and Mortality rate at 10x DC < 70%). A high level of resistance was also observed to carbamate (bendiocarb) with mortality rate at 5x DC < 25%). Aggravation of resistance was also noticed between 2009 and 2021. For pyrethroids, the mortality rate for permethrin reduced from 47.2% in 2009 to 13% in 2014 and 6.7% in 2021. For deltamethrin, the mortality rate reduced from 42.3% in 2009 to 1.75% in 2014 and 5.2% in 2021. For Bendiocarb, the mortality rate reduced from 60% in 2009 to 30.1% in 2014 and 12.2% in 2021. The high resistance observed is consistent with a drastic loss of pyrethroid-only bed nets efficacy although Piperonyl butoxide (PBO)-based nets remain effective. The resistance pattern observed was linked with high up-regulation of the P450 genes CYP6P9a, CYP6P9b and CYP6M7 in An. funestus s.s. mosquitoes surviving exposure to deltamethrin at 1x, 5x and 10x DC. A significant association was observed between the 6.5 kb structural variant and resistance escalation with homozygote resistant (SV+/SV+) more likely to survive exposure to 5x and 10x (OR = 4.1; P < 0.001) deltamethrin than heterozygotes. However, a significant proportion of mosquitoes survived the synergist assays with PBO suggesting that other mechanisms than P450s are present. Conclusions This resistance aggravation in An. funestus s.s. Malawian population highlights an urgent need to deploy novel control tools not relying on pyrethroids to improve the effectiveness of vector control.